Feed conversion efficiency does not negatively affect young sheep and ewe performance - De Barbieri, Ignacio; Navajas, Elly A.; Ramos, Zully; Ferreira, Gracialda; Velazco, José; Ciappesoni, Gabriel (Frontiers in Animal Science, 2024)
IntroductionImproving the feed efficiency (FE) in ruminants offers significant potential for optimizing the use of natural feed resource while simultaneously enhancing food and wool production. However, selecting for FE and high productivity may negatively impact the robustness traits, such as reproduction, health, and fat deposition, indicating potential antagonisms. This study evaluates the relationship between residual feed intake (RFI) and the productivity of yearling and adult ewes in extensive outdoor pastoral systems of three breeds.MethodsConducted from 2018 to 2022, the study included three cohorts (2018, 2019, and 2020) of ewe lambs from the Merino (435), Dohne (323), and Corriedale (215) breeds. In their first year, these lambs were phenotyped for feed intake, RFI, methane emissions, body weight and body weight, body condition score, fecal egg count, wool production, rib eye area, and fat thickness. Later, as hoggets or adult ewes, their body weight, body condition score, wool production, and reproductive traits were recorded. To examine the links between FE and performance, two contrasting groups (i.e., low 25% and top 75% quartiles) for RFI were analyzed.Results and discussionMore efficient animals had similar body weights and weight gains while consuming less feed than the less efficient ones. In addition, the wool production at 1 year of age, the resistance to gastrointestinal parasites (assessed by fecal egg count), and the daily methane emissions were unaffected by RFI group. Although no significant antagonisms were observed between yearling RFI and ewe reproduction, a trade-off with ewe fleece weight was identified. In conclusion, the more efficient animals demonstrated satisfactory performance under the evaluated conditions without compromising body weight, wool production (in yearlings), reproduction, or health.